2007
DOI: 10.1183/09031936.00152106
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PDGF, VEGF and FGF signalling attenuates fibrosis

Abstract: BIBF 1000 is a small molecule inhibitor targeting the receptor kinases of plateletderived growth factor (PDGF), basic fibroblast growth factor and vascular endothelial growth factor, which have known roles in the pathogenesis of pulmonary fibrosis.The anti-fibrotic potential of BIBF 1000 was determined in a rat model of bleomycin-induced lung fibrosis and in an ex vivo fibroblast differentiation assay. Rats exposed to a single intratracheal injection of bleomycin were treated with BIBF 1000 starting 10 days af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
266
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(277 citation statements)
references
References 64 publications
6
266
0
5
Order By: Relevance
“…These growth factors are known as fibrogenic mediators promoting fibroblast proliferation and matrix contraction. BIBF has been applied orally from day 10 to day 21 in the bleomycin treated rat model leading to reduced gene expression of transforming growth factor (TGF)-β1, procollagen-1, fibronectin and connective tissue growth factor (CTGF), as well as less collagen staining in treated animals compared to bleomycin controls (Chaudary NI, 2007). This compound is currently entering clinical trials in IPF.…”
Section: Hepatocyte Growth Factor (Hgf)mentioning
confidence: 99%
“…These growth factors are known as fibrogenic mediators promoting fibroblast proliferation and matrix contraction. BIBF has been applied orally from day 10 to day 21 in the bleomycin treated rat model leading to reduced gene expression of transforming growth factor (TGF)-β1, procollagen-1, fibronectin and connective tissue growth factor (CTGF), as well as less collagen staining in treated animals compared to bleomycin controls (Chaudary NI, 2007). This compound is currently entering clinical trials in IPF.…”
Section: Hepatocyte Growth Factor (Hgf)mentioning
confidence: 99%
“…Because TGF-β1 stimulation has been reported to induce α-SMA expression in fibroblasts as differentiation into myofibroblasts for 1 to 4 days, [19][20][21] we cultured the cells for 0 to 168 h (7 days) with TGF-β1 treatment to examine the effect of TGF-β1 on mRNA expression of α(IV) chains in TIG-1-20 cells at various time points. We confirmed that the mRNA expression of α1(IV) and α2(IV) chains was upregulated in TIG-1-20 cells up to 96 h (4days; Supplementary Figure 2).…”
Section: Deposition Of Type I Iii and Iv Collagens And α Chains Of mentioning
confidence: 99%
“…VEGF inhibition not only reduced the amount of scar formed but also improved the quality of the scar tissue by shifting the collagen fibril distribution in a manner that is similar to that of normal tissue. 21 The subconjunctival injection of bevacizumab was found to be associated with improvements in trabeculectomy bleb survival in glaucoma, which suggests that bevacizumab may be a useful agent for improving the success rate and limiting scar tissue formation after trabeculectomy. 22 This study aimed to evaluate the additive effect of bevacizumab to MMC-augmented trabeculectomy in recurrent cases of childhood glaucoma concerning its efficacy and complications.…”
Section: Discussionmentioning
confidence: 99%